2018
DOI: 10.1021/acs.cgd.8b00776
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy for the Morphology-Controlled Synthesis of V2O5 Microcrystals with Enhanced Capacitance as Battery-type Supercapacitor Electrodes

Abstract: Porous vanadium pentoxide (V2O5) microcrystals with different morphologies were synthesized through the decomposition of butterfly-like, rhombohedral, and flower-like ammonium metavanadate (NH4VO3) microcrystals, which were synthesized by the drowning-out crystallization of hydrothermal NH4VO3 aqueous solution using ethanol as both the antisolvent and the template for the self-assembly of vanadate ions. The effects of reaction conditions on the morphologies of products were characterized by scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 63 publications
(92 reference statements)
2
32
0
Order By: Relevance
“…45,46 The peaks at 284, 408, and 992 cm −1 correspond to the bending vibration of VO and stretching vibration of VO, respectively. 47,48 The consistent peak vibrations at 1346.8 and 1578.6 cm −1 are ascribed to the D-band and Gband of SWCNTs, which agree well with the previous XRD results. 49 Based on the high-resolution O 1s XPS spectra shown in Figure S1b, the fitted peaks situated at 530.35, 531.53, and 532.94 eV 19 are assigned to the different forms of O 2− in O− H, H 2 O, and C−O bonds, which also indicate that the water molecules have been imported successfully.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…45,46 The peaks at 284, 408, and 992 cm −1 correspond to the bending vibration of VO and stretching vibration of VO, respectively. 47,48 The consistent peak vibrations at 1346.8 and 1578.6 cm −1 are ascribed to the D-band and Gband of SWCNTs, which agree well with the previous XRD results. 49 Based on the high-resolution O 1s XPS spectra shown in Figure S1b, the fitted peaks situated at 530.35, 531.53, and 532.94 eV 19 are assigned to the different forms of O 2− in O− H, H 2 O, and C−O bonds, which also indicate that the water molecules have been imported successfully.…”
Section: Resultssupporting
confidence: 91%
“…Figure d shows the Raman spectra of the C/CaVOH sample. The peaks located at 143, 523, and 689 cm –1 are attributed to the stretching vibration of vanadyl bonds in VO 6 octahedra (V 2 O 2 ) n , V 3 –O bond, and V 2 –O, respectively, suggesting the unordered V–O–V bond in the main lattice. , The peaks at 284, 408, and 992 cm –1 correspond to the bending vibration of VO and stretching vibration of VO, respectively. , The consistent peak vibrations at 1346.8 and 1578.6 cm –1 are ascribed to the D-band and G-band of SWCNTs, which agree well with the previous XRD results …”
Section: Resultsmentioning
confidence: 95%
“…The electrochemical performance is largely determined by the physicochemical properties of the active electrode materials, such as morphologies, [ 23–28 ] porosity, [ 29–34 ] crystal structures, [ 35–39 ] and electrical conductivity. [ 40–45 ] Despite the advantages discussed above, the employment of TMOs for energy storage still encounters several difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Figure g revealed the CV curves of MCNO-4 at 5–80 mV s –1 , and those of MCNO-2 and MCNO-6 are shown in Figure S4e and S4g. The CV curves confirmed that the MCNO electrodes also have diffusion-controlled fast electrolyte ion transport and polarization. The GCD results at different current densities of MCNO-4 are displayed in Figure h, and those of MCNO-2 and MCNO-6 are shown in Figure S4d and S4h. The specific capacities of the MgCo 2 O 4 @NiMoO 4 electrodes were also calculated using formula 1 in the SI, further proving that the specific capacity of the MCNO-4 electrode is the largest, and detailed calculation results for each electrode are summarized in Table S3.…”
Section: Resultsmentioning
confidence: 67%